2010
DOI: 10.1007/s00415-009-5445-3
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral reduced sense of smell is an early indicator for global olfactory loss

Abstract: It is estimated that 15% of normosmic subjects demonstrate lateralized smell loss. The majority of individuals will not notice this difference between nostrils as long as olfactory function of the better nostril remains in the normal range. We were interested in the question whether subjects demonstrating clinically significant side differences of olfactory function are at risk to develop bilateral olfactory loss. Normosmic individuals with such side differences ("difference group", n = 35) were re-tested on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The healthy elderly subjects showed larger nostril side differences in the identification of odor when compared with younger subjects. Gudziol et al [37] also suggested that the individuals with nostril side differences of olfactory function are at risk to develop bilateral olfactory loss within 4.5 years. Further, the slow yogic breathing through left nostril may alleviate stress and reduce cardiovascular disease risks compared to right nostril breathing [38].…”
Section: Discussionmentioning
confidence: 99%
“…The healthy elderly subjects showed larger nostril side differences in the identification of odor when compared with younger subjects. Gudziol et al [37] also suggested that the individuals with nostril side differences of olfactory function are at risk to develop bilateral olfactory loss within 4.5 years. Further, the slow yogic breathing through left nostril may alleviate stress and reduce cardiovascular disease risks compared to right nostril breathing [38].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 15% of individuals with no complaints of decreased smell sensation demonstrate lateralized smell loss and most of them do not notice this as long as olfactory function of the better nostril remains within the normal range. 10 An injury to the secondary olfactory cortex such as the OFC results in a deficit of discrimination and recognition of odors. 11 OFC is found to have a critical role also in conscious olfactory perception.…”
Section: The Primary and Secondary Olfactory Cortices And Concepts Ofmentioning
confidence: 99%
“…[47][48][49]) oraz studiów klinicznych [50]. Ze względu na możliwość diagnozy różnych aspektów funkcjonowania węchu, SST może być bardzo przydatnym narzędziem zarówno dla praktyków, jak i naukowców zajmujących się węchem z bardziej teoretycznej perspektywy.…”
Section: Omówienieunclassified